Creating Work Life Balance And Burnout Prevention To Keep Employee Satisfaction - Ifah Finatry Latiep (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This study aims to determine the effect of work-life balance and burnout on job satisfaction either directly or indirectly which is carried out on employees of the BPJS Kesehatan Kedeputian Office in South Sulawesi, West Sulawesi, Southeast Sulawesi, and Maluku. This research uses a quantitative approach that intends to explain the position of the variables studied and the relationship between one variable and another with path analysis using the SmartPLS 3.2.8 program. The results of this study found that work life balance has a positive and significant effect on employee job satisfaction, burnout has a negative and significant effect on employee job satisfaction, work life balance has a positive and significant effect on employee job satisfaction if mediated by burnout. The conclusion shows that when the work life balance of an employee is well maintained, burnout can be reduced as soon as possible so as not to interfere with work. This can also affect the creation of job satisfaction when an employee can balance living conditions inside and outside the company